1988
DOI: 10.1007/bf00235194
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Na+-Ca2+ exchange in cardiac sarcolemmal vesicles by Ca2+ antagonists

Abstract: The purpose of this study was to examine the effect of three classes of Ca2+ antagonists, diltiazem, verapamil and nifedipine on Na+-Ca2+ exchange mechanism in the sarcolemmal vesicles isolated from canine heart. Na+-Ca2+ exchange and Ca2+ pump (ATP-dependent Ca2+ uptake) activities were assessed using the Millipore filtration technique. Sarcolemmal vesicles used in this study are estimated to consist of several subpopulations wherein 23% are inside-out and 55% are right side-out sealed vesicles in orientation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…That is, by potentiating SR Ca 2+ release through increased SR Ca 2+ load and fractional release. It is for this reason, and the well known promiscuity of available Ca 2+ channel antagonists 42, 43 that we have avoided experiments involving I CaL antagonists in this study. As such, we strongly recommend against interpreting the ability of I Ca L inhibitors to reduce EAD incidence in the mouse as inferring a role for I Ca L reactivation in driving murine EADs.…”
Section: Discussionmentioning
confidence: 99%
“…That is, by potentiating SR Ca 2+ release through increased SR Ca 2+ load and fractional release. It is for this reason, and the well known promiscuity of available Ca 2+ channel antagonists 42, 43 that we have avoided experiments involving I CaL antagonists in this study. As such, we strongly recommend against interpreting the ability of I Ca L inhibitors to reduce EAD incidence in the mouse as inferring a role for I Ca L reactivation in driving murine EADs.…”
Section: Discussionmentioning
confidence: 99%
“…Although nifedipine has other, nonchannel, effects at these concentrations, they should not account for the reduced accumulation. The bestestablished of these effects are inhibition of the Ca-ATPase (Hata et al, 1988) and inhibition of mitochondrial Na/Ca exchange (Vaghy et al, 1982) both of which would increase Ca accumulation. It has been suggested that nifedipine partially blocks plasmalemma Na/Ca exchange (Carvalho et al, 1986) which could account for the inhibition of influx, but in well-controlled studies on heart sarcolemma the drug does not affect this process (Hata et al, 1988).…”
Section: Calcium ~Flux During Ischcmiamentioning
confidence: 99%
“…4 -6 As in macrophage, 11 the L-type Ca 2ϩ antagonists also block the Na ϩ /Ca 2ϩ exchanger. 4,6,8 This exchanger is also present at the nuclear membranes 1 and could be also a target of some Ca 2ϩ blockers. Thus, in a cell type where a biophysical study of the L-type Ca 2ϩ channel was never demonstrated, the use of molecular biology techniques and/or L-type Ca 2ϩ channel blockers, as pharmacological specific tools for studying such a channel, should be carefully interpreted.…”
Section: S Everal Types Of Voltage-dependent Camentioning
confidence: 99%